2018
DOI: 10.7897/2230-8407.0911279
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Bacterial Activity of the Soil Fungal Metabolites

Abstract: Soil microbial communities are the most diverse group on earth possessing a plethora of activities useful to mankind. Fungal species in particular, produce secondary metabolites that are potential bioactive compounds. In the present study, fungal species isolated from the soils of Kolli Hills, Tamil Nadu were subjected to a primary screening for their antibacterial activity. Ten fungal strains were selected and their extracts were tested against pathogenic bacteria by disc diffusion method. The most efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These results support the finding of Singh et al (2012) and Kumari et al (2018) who found malt extract agar as the best medium. On the other hand, Bhagat et al (2016), (Thamilvanan et al (2018), Deka and Jha, (2018) and Toghueo et al (2018) reported the potato dextrose agar as the best medium for the maximum growth and production of metabolites. Kalyani et al (2016) found that the maximum growth and metabolite production Goutam et al (2016) reported that among the three organic solvents used, the crude metabolites of Aspergillus terreus (JAS-2) extracted using ethyl acetate Acinetobacter baumannii 12.5 ± 0.7 0 0…”
Section: Discussionmentioning
confidence: 99%
“…These results support the finding of Singh et al (2012) and Kumari et al (2018) who found malt extract agar as the best medium. On the other hand, Bhagat et al (2016), (Thamilvanan et al (2018), Deka and Jha, (2018) and Toghueo et al (2018) reported the potato dextrose agar as the best medium for the maximum growth and production of metabolites. Kalyani et al (2016) found that the maximum growth and metabolite production Goutam et al (2016) reported that among the three organic solvents used, the crude metabolites of Aspergillus terreus (JAS-2) extracted using ethyl acetate Acinetobacter baumannii 12.5 ± 0.7 0 0…”
Section: Discussionmentioning
confidence: 99%